Functional Comparison of Blood-Stage Plasmodium falciparum Malaria Vaccine Candidate Antigens - Illingworth, Joseph J.; Alanine, Daniel G.; Brown, Rebecca; Marshall, Jennifer M.; Bartlett, Helen E.; Silk, Sarah E.; Labbé, Geneviève M.; Quinkert, Doris; Cho, Jee Sun; Wendler, Jason P.; Pattinson, David J.; Barfod, Lea; et al. (Frontiers in Immunology, 2019)
The malaria genome encodes over 5000 proteins and many of these have also been proposed to be potential vaccine candidates, although few of these have been tested clinically. RH5 is one of the leading blood-stage Plasmodium falciparum malaria vaccine antigens and Phase I/II clinical trials of vaccines containing this antigen are currently underway. Its likely mechanism of action is to elicit antibodies that can neutralize merozoites by blocking their invasion of red blood cells (RBC). However, many other antigens could also elicit neutralizing antibodies against the merozoite, and most of these have never been compared directly to RH5. The objective of this study was to compare a range of blood stage antigens to RH5, to identify any antigens that outperform or synergize with anti-RH5 antibodies. We selected 55 gene products, covering 15 candidate antigens that have been described in the literature and 40 genes selected on the basis of bioinformatics functional prediction. We were able to make 20 protein-in-adjuvant vaccines from the original selection. Of these, S-antigen and CyRPA, robustly elicited antibodies with neutralizing properties. Anti-CyRPA IgG generally showed additive GIA with anti-RH5 IgG, although high levels of anti-CyRPA-specific rabbit polyclonal IgG were required to achieve 50 % GIA. Our data suggest that further vaccine antigen screening efforts are required to identify a second merozoite target with similar antibody-susceptibility to RH5.